Effects of Primary Caregivers’ Feeding Habits on the Nutrition Status of Pre-schoolers in Rupandehi District of Nepal - Sharma, Prakash; Budhathoki, Chitra Bahadur (Journal of Health Promotion, 2023)
Healthy food habits of primary caregivers may contribute to the overall growth, development, and optimal health of the ppreschoolers. This quantitative research aimed to examine the impact of the feeding practices of caregivers on nutritional status of 384 preschoolers (aged 36-71 months) in Rupandehi District of Nepal. The effects of feeding habit were compared with the nutritional status and thus the impact was examined. Information regarding socio-economic standing, demographics, feeding habits, and children’s nutrition statuses were collected through direct interviews and anthropometric measurement. The nutritional status of the children, including height-for-age (HAZ), weight-for-height (WAZ), and BMI-for-age z-scores (BAZ), was assessed using WHO Anthro, WHO Anthro Plus, and SPSS version 26 software. Statistical analysis involved Chi-square tests and logistic regression with a significance threshold established at p